2007
DOI: 10.1159/000106509
|View full text |Cite
|
Sign up to set email alerts
|

Antiglycation and Antioxidant Effect of Carnosine against Glucose Degradation Products in Peritoneal Mesothelial Cells

Abstract: Background/Aim:Toxicity with advanced glycation end products (AGEs) is a major problem in uremic patients. Treatment with peritoneal dialysis (PD) exacerbates AGE formation as a result of bioincompatibility of the conventional peritoneal dialysis fluid (PDF). The presence of glucose degradation products (GDPs) in PDF is the main cause of its bioincompatibility. Carnosine is an endogenous dipeptide with a powerful antiglycation/antioxidant activity. In an attempt to improve PDF biocompatibility, we evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 65 publications
2
28
0
Order By: Relevance
“…Cheng et al (2011) demonstrated in cultured neurons that MDA caused protein cross-linking and cytotoxicity, and that both these effects were reversed by carnosine treatment. Carnosine was found to enhance HPMC (human peritoneal mesothelial cells) viability against the toxic effect of RCS originated from glucose oxidation through the protection of cellular protein from modification and from ROS-mediated oxidative damage (Alhamdani et al 2007b). Regarding the in vivo evidence of carnosine to inhibit AGEs and ALEs formation, we recently found that carnosine treatment of Zucker rats for 24 weeks significantly reduced the urinary AGEs, protein carbonylation in the kidney and improved collagen solubility as an indicator of the extent of collagen crosslinking .…”
Section: Carnosine Prevents Ales and Ages Formationmentioning
confidence: 99%
“…Cheng et al (2011) demonstrated in cultured neurons that MDA caused protein cross-linking and cytotoxicity, and that both these effects were reversed by carnosine treatment. Carnosine was found to enhance HPMC (human peritoneal mesothelial cells) viability against the toxic effect of RCS originated from glucose oxidation through the protection of cellular protein from modification and from ROS-mediated oxidative damage (Alhamdani et al 2007b). Regarding the in vivo evidence of carnosine to inhibit AGEs and ALEs formation, we recently found that carnosine treatment of Zucker rats for 24 weeks significantly reduced the urinary AGEs, protein carbonylation in the kidney and improved collagen solubility as an indicator of the extent of collagen crosslinking .…”
Section: Carnosine Prevents Ales and Ages Formationmentioning
confidence: 99%
“…There is much evidence, mostly obtained from model systems, suggesting that carnosine can suppress protein modification mediated by reactive oxygen species (ROS) (Kohen et al, 1988;Boldyrev 2005;Alhamdani et al, 2007aAlhamdani et al, & 2007b, reactive nitrogen species (RNS) (Calabrese et al, 2005;Fontana et al, 2002), glycating agents (Hipkiss et al, 1995;Vinson and Howard, 1996;Seidler, 2000) and deleterious aldehydes such as malondialdehyde (Hipkiss et al 1997(Hipkiss et al and 1998a(Hipkiss et al and 1998b, hydroxynonenal (Aldini et al, 2002 and, acrolein Carini et al, 2003) and methylglyoxal (MG) (Hipkiss and Chana, 1998). Carnosine also inhibited the cross-linking of MG-modified protein with normal polypeptides (Hipkiss and Chana, 1998), most likely by forming adducts with the MG-induced protein carbonyl groups (Brownson and Hipkiss, 2000).…”
Section: Carnosine and Post-synthetic Protein Modificationmentioning
confidence: 99%
“…Of note, in a carnosine or beta-alanine supplementation study in rats with diet-induced obesity, it was recently demonstrated that plasma rather than muscle carnosine is involved in ameliorating high-fat diet-induced lipoxidative and inflammatory stress (Stegen et al 2015). Carnosine supplementation studies in murine models demonstrated therapeutic efficacy of carnosine to ameliorate diabetes and DN, as albuminuria and histological lesions were reduced after supplementation (Lee et al 2005;Alhamdani et al 2007;Sauerhöfer et al 2007;Riedl et al 2011;Aldini et al 2011;Nagai et al 2012;Peters et al 2012;Albrecht et al 2017).…”
Section: Introductionmentioning
confidence: 99%